Particles Ka(h) of Indonesian and Japanese: Cross Linguistic Study - Maharani Patria Ratna (IZUMI, 2020)
Some languages in the world have particles with their respective functions. One of them is Ka(h) particle which is used both in Indonesian and Japanese. Both are equally used as markers of the question sentence. In Indonesian the ka(h) particle is pronounced "Kah" while in Japanese it is pronounced "Ka.” The purpose of this study is to identify what are the similarities and differences in the use of Ka(h) particles in Indonesian and Japanese. the data is taken by a literature study in Indonesian linguistics and Japanese linguistics. These similarities and differences will be studied through aspects of characteristics, function, location, and intonation. Both particles are enclitic and arbitrary, but only Kah particle has a free distribution characteristic. On the function of point of view, both particles are question marker, but only The Ka particle functioned as a choice marker and indefinite pronoun. The results of this study indicate that in Indonesian the use of Kah particles is always pronounced with rising intonation, whereas in Japanese the "ka" particle can be pronounced with rising or falling intonation. Also both particles can be located in the middle and at the end of the sentence.